ChemInform Abstract: Palladium‐Catalyzed Asymmetric Hydrosilylation of Styrene and Its Derivatives with Chiral Phosphoramidite Ligands Containing Chiral Ferrocenyl Amine. Issue 42 (September 2016) - Park, Hyun‐Sub; Kim, Min Young; Ahn, Hyo Jin; Han, Jin Wook
Abstract: Asymmetric hydrosilylation of styrene and its derivatives (I) is accomplished using a palladium catalyst with the title ligand.